2009
DOI: 10.1007/s12224-009-9053-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship Between Clonal Traits and Small-Scale Spatial Patterns of Three Dominant Grasses and its Consequences on Community Diversity

Abstract: In a secondary successional community, we focused on the role of local dispersion mediated by clonal growth in the density and spatial patterning of tillers of three dominant grass species (Elymus repens, Brachypodium pinnatum and Calamagrostis epigejos) on the plant neighbourhood scale. We also asked whether the spatial pattern/density of their tillers were linked to the local diversity structure. In ten 75 cm×75 cm quadrats for each of the three species, we quantified i) the clonal morphology patterns from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…The relationships between environmental factors, clonal traits and spatial aggregation, which we have highlighted in this study, support the idea of a continuum between phalanx and guerrilla growth forms that can operate at the intraspecific level. Here, we also emphasize the importance of the number of clumping tillers as an additional and independent trait from spacer length (Pottier & Evette 2010). Indeed, this trait was statistically independent from spacer length in regard to the standardized PCA and different developmental origin (i.e.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The relationships between environmental factors, clonal traits and spatial aggregation, which we have highlighted in this study, support the idea of a continuum between phalanx and guerrilla growth forms that can operate at the intraspecific level. Here, we also emphasize the importance of the number of clumping tillers as an additional and independent trait from spacer length (Pottier & Evette 2010). Indeed, this trait was statistically independent from spacer length in regard to the standardized PCA and different developmental origin (i.e.…”
Section: Discussionmentioning
confidence: 85%
“…Carex curvula in alpine ecosystems Steinger et al 1996); on intermediate scales in plant communities (Lovett Doust 1981; Pottier et al 2007); and on much finer scales of a few centimetres (e.g. Law et al 1997; Pottier & Evette 2010). Here, we showed that even on a very narrow range of scales (from 1 cm × 1 cm to 7.5 cm × 7.5 cm), intravaginal tillering and extravaginal tillering had differential consequences for tiller clumping when the grain size of observations changed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to date, including plastic response to changeable light conditions (Mojzes et al, 2003), high tiller density and branching frequency (Pottier and Evette, 2010), and its capacity for early-season clonal growth and a strategy of clonal integration (de Kroon and Bobbink, 1997;de Kroon and Knops, 1990). Its increasing abundance and biomass is associated with elevated nitrogen and phosphorus input to the soil (Willems and van Nieuwstadt, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Among other mechanisms underlying the success of clonal plants are fitness gains enhanced through sex allocation (Dorken and van Drunen 2010), shoot/root correlations (Sachs 2008), and balance and triggering between sexual and asexual reproduction (Zhang and Zhang 2007;Honnary and Jacquemyn 2010;Schulze et al 2012). Although there are some recent studies investigating the community effects of clonality (Pottier and Evette 2010;Cushman and Gaffiney 2010;Yu et al 2010;Canullo et al 2011;Herben and Wildova´2012), the impact of clonality on community structure and dynamics still needs to be well documented in order to understand the roles and mechanisms of clonal plants in maintaining various ecosystems on Earth. While clonality has been the focus of much research, and many studies have examined the effects of clonality, e.g., clonal integration on the growth of individual clonal plants, relatively few studies have tested the community level effects of clonality.…”
Section: Introductionmentioning
confidence: 99%